PEMBERDAYAAN MASYARAKAT MELALUI SELEKSI GALUR MURNI DAN BUDIDAYA ITIK KAMANG BERBASIS SUMBER DAYA LOKAL SEBAGAI DASAR PENETAPAN RUMPUN DAN KONSERVASI PLASMA NUTFAH ITIK LOKAL DI KECAMATAN TILATANG KAMANG - Firda Arlina; Sabrina Sabrina (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2018)
Kamang duck is a local poultry germ plasm of West Sumatra originating from Tilatang Kamang District. The number of 31 students from various faculties held in this program. This activity aims to provide a technology package of mating systems and management of hatcheries to improve the productivity of Kamang duck. in addition it also provides training for the processing of eggs and un productive Kamang duck to become innovation product like rendang egg and rendang suir, and feed processing technologies base on locally sourced. The final goal was to increase productivity, and efficiency of processing livestock feed costs for the development and preservation of germplasm Kamang duck well as an increase in the income of livestock in Koto Kanagarian Tangah District of Tilatang Kamang. The method used in this service program is counseling, demonstration, training, coaching and the provision of technological packages, as well as observation and evaluation and data collection to measure the parameters of the success of the programs. The implementation of KKN PPM starts from pre-KKN, survey and implementation in the field for 40 days, starting from 14th July until 14th August 2017. The result of activity got very positive response from society, government and related offices. KKN-PPM program activity was conducted on four region in Koto Tangah village Tilatang Kamang, Agam District of West Sumatra, namely